2014
DOI: 10.1007/jhep02(2014)004
|View full text |Cite
|
Sign up to set email alerts
|

Transverse-momentum spectra of electroweak bosons near threshold at NNLO

Abstract: Abstract:We obtain the next-to-next-to-leading order corrections to transversemomentum spectra of W , Z and Higgs bosons near the partonic threshold. In the threshold limit, the electroweak boson recoils against a low-mass jet and all radiation is either soft, or collinear to the jet or the beam directions. We extract the virtual corrections from known results for the relevant two-loop four-point amplitudes and combine them with the soft and collinear two-loop functions as defined in Soft-Collinear Effective T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 74 publications
2
47
0
Order By: Relevance
“…The resummation of logarithms should therefore only be a moderate effect. This observation was made earlier in [12,28,29], where it was found that resummation has a small effect on the central value but leads to somewhat reduced scale uncertainties. One sees from the plots that the scales determined from the NLO and NNLO corrections are almost identical, as they should be if there is a natural scale associated with the corrections.…”
Section: Jhep11(2014)026supporting
confidence: 61%
See 4 more Smart Citations
“…The resummation of logarithms should therefore only be a moderate effect. This observation was made earlier in [12,28,29], where it was found that resummation has a small effect on the central value but leads to somewhat reduced scale uncertainties. One sees from the plots that the scales determined from the NLO and NNLO corrections are almost identical, as they should be if there is a natural scale associated with the corrections.…”
Section: Jhep11(2014)026supporting
confidence: 61%
“…What is also obvious from the plots is that all of the NNLO corrections to Z-production are small as long as the scales are chosen properly. Indeed, we found in [12] that the two-loop corrections to W and Z production are moderate, of the order of 5%.…”
Section: Jhep11(2014)026mentioning
confidence: 86%
See 3 more Smart Citations